Identifying periodicity in nurse call occurrence: Analysing nurse call logs to obtain information for data‐based nursing management. (18th February 2021) - Fukushige, Haruna; Ishii, Atsue; Inoue, Yoshiaki; Yamaguchi, Akiko; Hosona, Mio; McCarthy, Kinuko; Williamson, Akiko; Taniura, Yoko; Nakashima, Keisuke
Abstract: Aim: To verify our hypothesis that 'there is periodicity in nurse call occurrence'. Background: It is difficult to plan nursing management because nursing tasks can vary widely, seemingly at random. One of the most useful pieces of information for decision‐making is periodicity. If periodicity is present, it should be possible to predict the occurrence of tasks and make preventive strategies. In this study, we focused on the nurse call, which plays an important role in nursing practice. Method: We used nurse call logs that accumulated automatically when patients pushed the button. Data were obtained from 1 January 2014 to 30 September 2017 (1, 369 days) in a university hospital. The total number was 5, 982, 935. Periodicity was verified by the autocorrelation function. Results: The value of the autocorrelation function increased regularly, which demonstrates there was periodicity in nurse call occurrence. Conclusion: Our hypothesis was accepted. The presence of periodicity indicates that nurse call occurrence is not a random event but has a pattern. Implications for Nursing Management: If we can identify patterns such as the time that nurse calls frequently occur, managers can implement two strategies: one, assigning more nurses and two, moving tasks other than nurse calls to another time.